2010
DOI: 10.1260/2041-4196.1.2.219
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Underpressure Phase on the Dynamic Response of Structures Subjected to Blast Loads

Abstract: The standard approach in protective design is to model blast loads with a triangular pulse shape which is characterized by the peak reflected overpressure and the reflected impulse. The US and European threat levels, GSA and ISO EXV, define pressure-impulse combinations for blast load characterization. However, this approach neglects the underpressure phase. The actual decay of a blast load is nonlinear and can be modeled more accurately with an exponential approach which takes into account the underpressure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 10 publications
1
32
0
1
Order By: Relevance
“…This can be seen in the reflection coefficient plot in Figure 2(a) -the reflection coefficient is invariant of angle of incidence for θ ≤ 45° at small incident overpressures (i.e. those expected in tests [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Secondly, the tests in which the gauges were located at large angles of incidence (θ ≥ 45°) lie within a narrow band of scaled distances, over which the angle of incidence effects will be relatively constant.…”
Section: Resultsmentioning
confidence: 83%
“…This can be seen in the reflection coefficient plot in Figure 2(a) -the reflection coefficient is invariant of angle of incidence for θ ≤ 45° at small incident overpressures (i.e. those expected in tests [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Secondly, the tests in which the gauges were located at large angles of incidence (θ ≥ 45°) lie within a narrow band of scaled distances, over which the angle of incidence effects will be relatively constant.…”
Section: Resultsmentioning
confidence: 83%
“…Teich and Gebbeken [7] took a more general approach by conducting a parametric study on elastic single-degree-of-freedom (SDOF) systems to quantify the effect of the negative phase relative to the effect of the positive phase alone. It was found that for certain configurations of scaled distance and dynamic target properties, inclusion of the negative phase in the model could cause midspan displacement of up to an order of magnitude greater than that of the positive phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to better control the form of the negative phase, Teich & Gebbeken [7] introduce the negative phase reflection coefficient, Cr , which is a function of the scaled distance,…”
Section: Extended Friedlander With Teich Crmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of load duration to natural period is roughly 0.1; the loading is highly impulsive and, particularly with far-field loading, inclusion of the negative phase for impulsive analyses is important (Teich & Gebbeken 2010). When the load is modelled as a full positive and negative phase pressure, the inclusion of the negative phase enables the SDOF model to predict the peak response of the non-cleared plates to a sufficient level of accuracy.…”
Section: Single-degree-of-freedom Responsementioning
confidence: 99%